Peran Guru Akidah Akhlak Dalam Meningkatkan Akhlaqul Karimah Siswa di Era Society 5.0 - Tiara Lubis; Rahmatun Nisa; Salniati Nasution; Eka satya; Rizka Amanda Putri; Inom Nasution; Saila Rahma Annisa Nasution (Al-Tarbiyah : Jurnal Ilmu Pendidikan Islam, 2024)
This narrative study aims to explain the role of faith teachersin improving students morals in the era of society5.0. the data in this research was obtained from the results of a semi structured interview with a teacher of moral beliefs. This study found three important data themes, namely the impact of technology on student morals, problems experienced by teachersin inimproving student morals, and efforts made by teachers to improve students moral. It it hoped that these findings will provide solution information students morals in this era of society.